Relationship between the number of comorbidities, quality of life, and cardiac autonomic modulation in patients with coronary disease: a cross-sectional study - Valente, Heloisa Balotari [UNESP]; dos Santos Silva, Vitor Eduardo [UNESP]; Barros, Thamyres Rangel Mendes [UNESP]; Vanderlei, Franciele Marques [UNESP]; Laurino, M. J.L. [UNESP]; Botta, Ana Flavia Balotari [UNESP]; Vanzella, Laís Manata; Bongiovani, Antonio Claudio; Vanderlei, Luiz Carlos Marques [UNESP] (FapUNIFESP (SciELO), 2022)
OBJECTIVE: The aim of this study was to evaluate if there is a relationship between the number of comorbidities, autonomic modulation, and quality of life in patients diagnosed with coronary artery disease. METHODS: A cross-sectional study was conducted at an outpatient rehabilitation center in Presidente Prudente-SP, Brazil. A total of 27 participants (65.33±9.23 years) diagnosed with coronary artery disease were assessed, from a cardiac rehabilitation program, independent of sex or age. The number of comorbidities was evaluated using the Self-Administered Comorbidity Questionnaire, and quality of life was evaluated using the Medical Outcome Study 36-Item Short Form Health Survey (SF-36) (eight domains: functional capacity, physical aspects, pain, general health status, vitality, social aspects, emotional aspects, and mental health). To evaluate the cardiac autonomic modulation, the heart rate was registered beat to beat using an heart rate monitor in the supine position during rest for 30 min. A total of 1000 RR intervals were considered to calculate linear (time domain: RMSSD, SDNN; frequency domain: LF, HF, LF/HF) and nonlinear indices (SD1, SD2, SD1/SD2) of heart rate variability. RESULTS: A negative correlation was observed between the aggregation of comorbidities and the pain domain of the SF-36 (r=-0.427; p=0.03). No significant correlations were observed between other variables (p>0.05). CONCLUSION: The number of comorbidities is inversely related to the pain domain of the SF-36, suggesting that a higher pain level is related to a higher number of comorbidities in coronary artery disease patients.
Keywords: Chronic disease; Comorbidity; Coronary artery disease; Heart rate; Quality of life